Análise documental das linhas prioritárias propostas por organizações articuladas com a construção sustentável brasileira - Bassetto, Luci Ines (2016)
The central theme of this study refers to Sustainable Construction from the perspective of Ecological Sustainability, passing by themes of the role of Civil Construction as a transforming and regenerative agent of their ecological impacts in society. It is perceived a conflict between Ecological Sustainability and Sustainable Development due the later suggest economic growth with care for environment and social issues. Despite already identified planetary boundaries, in Brazil, the way to understand the Civil Construction as social and economic transformation agent is still not in favor of maintaining the nature balance. With different characteristics, the country presents action priorities on sanitation, water, forest exploration and food production that should be incorporated into their strategies. Although the term "sustainable construction" refer to environmental concern in the sector, the common basis of debate is still beginner. The objective was to analyze published documents on priority lines of discussions among representative agents of Brazilian Civil Construction sector to examine the focus of Ecological Sustainability as a support basis for life on the planet. It were considered contributions from public policies of "sustainable construction" to stimulate the production chain to increase sustainability. It is believed that this study can promote an analysis of the importance of ecological sustainability in "sustainable construction" through production of innovation, knowledge and expertise. The study methodology has a qualitative approach, theoretical and conceptual nature having as object of analysis public and private documents. It was identified convergences and divergences in debates relevant to introduce advances in the discussion. The content identified in documents is limited to the importance of civil construction in urban development and to supply resulting habitation shortage without reference to privileged groups, such as stated in Agenda 21 for sustainable development in developing countries. When referring to actions aligned with sustainable development, the texts abstain of references to the issue of social inclusion in habitation. The particularities of the three documents are presented as true and relevant to the construction sector. Considering documents content, companies that take care of water, energy and the environment, can be more competitive and improve their productivity and profitability. It was concluded that the documents are initiatives of reflections on the theme of Ecological Sustainability and provide guidance for the balance of sustainable development, which can be achieved by the principles of circular economy applied to Sustainable Construction. As suggestions for future works, this thesis emphasized the importance of circular economy as an alternative to align interests of economic development and sustainable development through Sustainable Construction.